Alpha-1 Antitrypsin Z Variant (AAT PI*Z) as a Risk Factor for Intrahepatic Cholestasis of Pregnancy - Kosinski, Przemyslaw; Kedzia, Malgorzata; Mostowska, Adrianna; Gutaj, Pawel; Lipa, Michal; Wender-Ozegowska, Ewa; Rozy, Adriana; Chorostowska-Wynimko, Joanna; Wielgos, Miroslaw; Jezela-Stanek, Aleksandra (Frontiers in Genetics, 2021)
Background: Intrahepatic cholestasis of pregnancy (prevalence 0.2% – 15.6%) is the most common pregnan-cy-related liver disorder. It may have serious consequences for a pregnancy, including increased risk of preterm delivery, meconium staining of amniotic fluid, fetal bradycardia, distress, and fetal demise. In cases of high bile acids (>100 μmol/L), patients have 10-fold increase in the risk of stillbirth. Biophysical methods of fetal monitoring, such as cardiotocography, ultrasonography or Doppler have been proven unreliable for risk prediction in the course of in-trahepatic cholestasis. Therefore, we believe extensive research for more specific, especially early, markers should be carried out. By analogy with cholestasis in children with inherited alpha-1 antitrypsin deficiency, we hypothesized the SERPINA1 Z pathogenic variant might be related to a higher risk of cholestasis in pregnancy. This study aimed to investigate the most common alpha-1 antitrypsin deficiency variants (Z and S SERPINA1 alleles) in a group of cho-lestatic pregnant women. Results: The Z carrier frequency was calculated to be 6,8%, which is much higher compared to the general population (2.3%) (the Chi-squared test with Yates correction is 6.8774 [p=0.008]).Conclusions: Increased prevalence of SERPINA1 PI*Z variant in a group of women with intrahepatic cholestasis may suggest a possible genetic origin of a higher risk of intrahepatic cholestasis in pregnancy.